A link between irritable bowel syndrome and fibromyalgia may be related to findings on lactulose breath testing. Issue 4 (12th March 2004) - Pimentel, M; Wallace, D; Hallegua, D; Chow, E; Kong, Y; Park, S; Lin, H C
Abstract : Background: An association between irritable bowel syndrome (IBS) and small intestinal bacterial overgrowth (SIBO) has been found. Objective: To compare the prevalence and test results for bacterial overgrowth between IBS and fibromyalgia. Methods: Subjects with independent fibromyalgia and IBS were compared with controls in a double blind study. Participants completed a questionnaire, and a lactulose hydrogen breath test was used to determine the presence of SIBO. The prevalence of an abnormal breath test was compared between study participants. Hydrogen production on the breath test was compared between subjects with IBS and fibromyalgia. The somatic pain visual analogue score of subjects with fibromyalgia was compared with their degree of hydrogen production. Results: 3/15 (20%) controls had an abnormal breath test compared with 93/111 (84%) subjects with IBS (p<0.01) and 42/42 (100%) with fibromyalgia (p<0.0001 v controls, p<0.05 v IBS). Subjects with fibromyalgia had higher hydrogen profiles (p<0.01), peak hydrogen (p<0.0001), and area under the curve (p<0.01) than subjects with IBS. This was not dependent on the higher prevalence of an abnormal breath test. The degree of somatic pain in fibromyalgia correlated significantly with the hydrogen level seen on the breath test ( r  = 0.42, p<0.01). Conclusions: An abnormal lactulose breath test is more common in fibromyalgia than IBS. In contrast with IBS, the degree of abnormality on breath test is greater in subjects with fibromyalgia and correlates with somatic pain.